2016
DOI: 10.1111/all.12869
|View full text |Cite
|
Sign up to set email alerts
|

Identification of STOML2 as a putative novel asthma risk gene associated with IL6R

Abstract: Background Functional variants in the interleukin-6 receptor gene (IL6R) are associated with asthma risk. We hypothesized that genes co-expressed with IL6R might also be regulated by genetic polymorphisms that are associated with asthma risk. The aim of this study was to identify such genes. Methods To identify genes whose expression was correlated with that of IL6R, we analyzed gene expression levels generated for 373 human lymphoblastoid cell lines by the Geuvadis consortium, and for 38 hematopoietic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…(Figure 4b). BCL6 modulates the response of interleukin 4, known to be involved in asthma 63 , and has been linked to asthma in mice 64 and humans 65 , but to our knowledge BCL6 has not previously been implicated as an asthma gene using GWAS data. BCL6 was implicated by 3 of the functionally informed S2G strategies used by cS2G, including EpiMap enhancer-gene linking in common myeloid progenitor CD34+ cells (for rs509399 only), identified by LDSC-SEG 50 as a critical cell-type for asthma (P = 1.2 x 10 -4 ; see Methods; also see ref.…”
Section: Leveraging the Combined S2g Strategy To Pinpoint Disease Genesmentioning
confidence: 84%
“…(Figure 4b). BCL6 modulates the response of interleukin 4, known to be involved in asthma 63 , and has been linked to asthma in mice 64 and humans 65 , but to our knowledge BCL6 has not previously been implicated as an asthma gene using GWAS data. BCL6 was implicated by 3 of the functionally informed S2G strategies used by cS2G, including EpiMap enhancer-gene linking in common myeloid progenitor CD34+ cells (for rs509399 only), identified by LDSC-SEG 50 as a critical cell-type for asthma (P = 1.2 x 10 -4 ; see Methods; also see ref.…”
Section: Leveraging the Combined S2g Strategy To Pinpoint Disease Genesmentioning
confidence: 84%
“…STOML2 is a gene that plays a key role in mitochondrial function and T-cell activation. Recently, the expression of STOML2 was negatively correlated with that of the IL6R, which has been implicated in asthma pathophysiology, and the increased expression of STOML2 was associated with an increased asthma risk by RNA-seq analysis 32. The exact roles and mechanisms of HDAC10, STOML2, and other genes in COPD, especially in early stages of the disease, need to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the expression of STOML2 was negatively correlated with that of the IL6R, which has been implicated in asthma pathophysiology, and the increased expression of STOML2 was associated with an increased asthma risk by RNA-seq analysis. 32 The exact roles and mechanisms of HDAC10, STOML2, and other genes in COPD, especially in early stages of the disease, need to be clarified in future studies. BAX, an apoptosis regulator, is a marker of upregulated apoptosis in COPD, and it was found to downregulated in the COPD without emphysema group compared with that in healthy smokers in the present study, contrary to a previous report that patients with emphysema showed a significant increase in the Bax index.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Hirschfield et al observed the association between primary biliary cirrhosis and variants of immune regulatory gene CLEC16A (Hirschfield et al, 2012). Besides, CLEC16A polymorphisms may involve in pathogenesis of allergic diseases (Revez et al, 2016;Ashley et al, 2017), which can increase or decrease susceptibility to AR through interleukin, and other genes (Black et al, 2009). In an article reported by Ferreira et al, they observed CLEC16A rs62026376 associated with increased asthma with hay fever risk (Ferreira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%